Modern learning approaches in higher education: A review of the literature - Sattarova Ulkar; Groot Wim; Arsenijević Jelena (Zbornik Instituta za pedagoška istraživanja, 2020)
This paper provides a review of the literature on the evaluation of two learning approaches in higher education: problem-based learning (PBL) and student-centred learning (SCL). We were interested in dissemination of these learning approaches in higher education in both developing and developed countries. We identified 47 experimental and quasi-experimental studies published before March 2020, from medical, engineering and other fields of higher education. Historically PBL has been mostly applied in medical, health and related disciplines. Over the years, PBL and SCL have been successfully applied in other disciplines as well. Articles on university policy-making and historical-analytical ones are included too. Around 70% of the articles have an experimental design. Sample sizes range from 15 to 1404 persons, including both students and tutors. Most of the studies report positive outcomes. We aimed to show whether PBL and SCL can be effectively applied in engineering and other fields worldwide (in both developing and developed countries), as many polytechnic and engineering universities are debating concerning new learning approaches. It is evident from the articles in the review that these approaches need to be adapted depending on the field of education and the initial conditions (evaluation rules, level of familiarisation with these approaches of students) in the university. Besides, most authors are interested in the modernisation of these approaches.